2010
DOI: 10.1103/physrevd.82.124003
|View full text |Cite
|
Sign up to set email alerts
|

Substructure lensing in galaxy clusters as a constraint on low-mass sterile neutrinos in tensor-vector-scalar theory: The straight arc of Abell 2390

Abstract: Certain covariant theories of the modified Newtonian dynamics paradigm seem to require an additional hot dark matter (HDM) component -in the form of either heavy ordinary neutrinos or more recently light sterile neutrinos (SNs) with a mass around 11eV -to be relieved of problems ranging from cosmological scales down to intermediate ones relevant for galaxy clusters. Here we suggest using gravitational lensing by galaxy clusters to test such a marriage of neutrino HDM and modified gravity, adopting the framewor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 140 publications
(251 reference statements)
1
7
0
Order By: Relevance
“…Some of the dynamical mass must be provided, as expected, by the central galaxies, but the required amount implies a mass-to-light ratio of 1.2M ⊙ /L ⊙ in the K band, in agreement with stellar population synthesis models. An 11 eV sterile neutrino is also consistent with the straight arc, originated by a strong lensing effect, observed in the cluster A2390 [49].…”
Section: The Role Of An 11 Ev Sterile Neutrinosupporting
confidence: 80%
“…Some of the dynamical mass must be provided, as expected, by the central galaxies, but the required amount implies a mass-to-light ratio of 1.2M ⊙ /L ⊙ in the K band, in agreement with stellar population synthesis models. An 11 eV sterile neutrino is also consistent with the straight arc, originated by a strong lensing effect, observed in the cluster A2390 [49].…”
Section: The Role Of An 11 Ev Sterile Neutrinosupporting
confidence: 80%
“…Again, it was shown that the density of missing mass was compatible with 2 eV ordinary neutrinos, like in most clusters with T > 4 keV [140]. Finally, let us note that strong lensing was also recently used as a robust probe of the matter distribution on scales of 100 kpc in galaxy clusters, especially in the cluster Abell 2390 [150]. A residual missing mass was again found, compatible with the densities provided by fermionic hot dark matter candidates only for masses of ∼ 10 eV and heavier.…”
Section: Strong and Weak Lensing By Galaxy Clustersmentioning
confidence: 84%
“…1) in small galaxies and in the solar system [14]. Additionally, there will be only very mild (< 50%) variations of A 0 inside galaxies, as well as between galaxies, small variations which might be desirable to explain some anomalies in strong lensing galaxies [15][16][17][18][19]. In any case this scatter is acceptable as the MOND formula works for all galaxies as long as a 0 is within the range between 0.9 and 1.7 × 10 −10 m s −2 [13,20].…”
Section: A Realistic Effective Variation Of the Acceleration Scalementioning
confidence: 99%